Effect of fruit juices in skim milk extender in maintaining Sapudi ram spermatozoa quality at chilled temperature - Retta, Ayun Tria Marga; Suherni Susilowati; Sri Pantja Madyawati; Tatik Hernawati; Wurlina Wurlina; Retno Sri Wahjuni (Ovozoa: Journal of Animal Reproduction, 2022)
This study aimed to determine the effect of the addition of cherry tomato, california papaya, and honey melon juice into skim milk extender in maintaining the quality of Sapudi ram semen at chilled temperature (5oC) storage. Five replication of ejaculates were divided equally into four groups. In control group (T0) semen was diluted in skim milk extender, while in T1, T2, and T3 groups semen were diluted in skim milk extender contained 20% of cherry tomato, california papaya, and honey melon juice, respectively. The extended semen was stored at a chilled temperature, and semen quality (based on sperm motility, viability, and plasma membrane integrity) was observed daily for five days. The result showed that semen quality declined day by day during the five days of storage. Based on the minimum standard of post-thawed semen motility (40%), the spermatozoa of the control group only lasted by the second day. Meanwhile, in the groups with the addition of fruit juice motility could last up to the third day, with the highest motility (p <0.05) on the addition of california papaya juice. This study concluded that the addition of 20% (v/v) california papaya juice in skim milk extender could maintain the percentage of spermatozoa motility up to three days at a chilled temperature.